Psychological Transformation by an Intervention to Facilitate Benefit Finding Among People With Chronic Mental Illness in Japan. Issue 2 (13th March 2015) - Chiba, Rie; Miyamoto, Yuki; Harada, Naoko
Abstract : Purpose: This study aimed to preliminarily explore the psychological transformation effected by a newly developed intervention program for facilitating benefit finding among individuals with chronic mental illness in Japan. Design and Methods: An intervention study with three weekly group sessions was implemented, and qualitative data on the participants' experience of benefit finding were obtained by a questionnaire survey and analyzed using content analysis technique. Findings: Of the 31 participants, 23 responded that they realized some sort of benefit finding through the intervention. Practice Implications: The program component in question may contribute to enhanced benefit finding for people with chronic mental illness while longitudinal studies involving more participants are desirable.